Advances in Smart Materials and Structures - Wang, Bing; Lee, Tung Lik; Qin, Yang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Smart materials and structures are capable of active or passive changes in terms of shapes, properties, and mechanical or electromagnetic responses in reaction to an external stimulus, such as light, temperature, stress, moisture, pH, and electric or magnetic fields. They have attracted increasing interest for their enhanced performance and efficiency over a wide range of industrial applications, especially for aerospace. These require novel engineering approaches and design philosophies in order to integrate the actions of sensors, actuators, and control circuit elements into a single system that can respond adaptively to its surroundings. This reprint has collected cutting-edge research and recent advances in smart materials and structures, including seven original research papers and three review articles, co-authored by 65 scientists and engineers from 18 institutions and 3 industries. The research topics mainly cover advanced materials, applications of smart materials and structures, as well as recent development in sensing techniques. We hope this reprint will contribute to disseminating the latest progress in smart materials and structures, as well as stimulate the interest of its audience to work in this important and vibrant area to promote and benefit the multidisciplinary scientific communities.